Spatiotemporal Characteristics of Long-Term Annual Average Air Temperature over Sri Lanka - Wijeratne, V.P.I.S.; Manawadu, L.; Kaushalya, G.N. (International Journal of Multidisciplinary and Current Educational Research (IJMCER), 2020)
Air Temperature plays an important role in perceiving climate change over the world caused by many physiographic and anthropogenic activities. The most recent climate change related studies have focused on changes of metrological variables such as temperature and precipitation. This research mainly aimed to examine the spatiotemporal variation of the annual average air temperature over Sri Lanka from 1981 to 2019. The NASA POWER weather database were used to extract the annual average temperature for 57 major and minor observatories in Sri Lanka. Spatial interpolation techniques, cluster and outlier analysis in ArcGIS, regression analysis and standard deviation method were used to fulfill the study objectives. The result of this research revealed that the annual mean air temperature of the country has slightly increased from 0.85oC during the last 39 years. Jaffna is the area which shows highest increment (0.84oC) of air temperature and NuwaraEliya shows the lowest increment of air temperature (0.77oC) in the country during the study period. Also, it can be identified that there are a few extremes of annual mean air temperature and those extremes can be well correlated with the impact of El Niño and La Niño. In the decade of 2001 to2010, the temperature has shown downward trend and after 2010 again it has shown upward trend until 2019. Also, two distinct clusters were identified in the northwest and middle part of the country and most of the meteorological stations located in the country have shown an increasing trend of annual air temperature from 1981 to 2019.
Keywords: Air Temperature; NASA Power weather data